Pendidikan Islam Berwawasan Multikultural di Sekolah/Madrasah - Azmi Purba, Fauzul; Albina, Meyniar (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article discusses the Policy Analysis of Multicultural Insights in Islamic Education in Schools/Madrasah, in the study of Islamic religious education policies, which focus on the challenges and opportunities for implementing multi-cultural Islamic religious education policies in schools /madrasah. The results of the study show that the core values of multicultural education are: appreciation of the reality of cultural plurality in society; recognition of human dignity and human rights; development of the responsibility of the world community, and the development of human responsibility towards planet earth. The substance is explained in the seven values of Islamic education with multi-cultural perspective, namely; andragogical value, peace, inclusion, kearipan, tolerance, humanism and freedom. These four domains, as a condition for increasing humanist, pluralist and democratic behavior. He explained, beginning with the basic concept, the policy and the urgency of multi-cultural education education, the implementation of multi-cultural education education policies and the problems it faces. Analysis of challenges and opportunities for policy implementation. Ended with the potential of multi-cultural Islamic religious education in schools / madrasah